Katekese Digital: Membangun Komunitas Belajar Katekese Melalui Teknologi - Karolina Suwul; Emeria Tarihoran (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Humans are social creatureswho need interaction with other people to build their lives. Shared life emphasizes love that comes from God. People are not only involved in certain communities, people must also be more involved in the life of the Church. Their involvement in Church life is about how they actively participate in strengthening their spiritual bond with God. The advancement of digital technology in society has caused many people to utilize modern technology in carrying out catechetical activities because of the importance of building society’s faith in the digital era. Learning catechesis with various new services, both for the general public and small groups, will facilitate and encourage their ability to understand technology and their faith in God. Catechesis is a systematic and planned process in pastoral activities, catechesis has its own goal, namely to maintain, develop and mature the faith of the people through a systematic and planned teaching process so that people will increasingly live in the fullness of their faith in Jesus Christ and live according to his will (cf. CT. arts 20-21). The experience of using social media generally provided benefits for who felt they gained insight and were strengthened in the religious identity of the people. People see social media as a means to apostolic role with various spiritual content.